Pengaruh Intradialitic Exercise Terhadap Hipertensi Intradialytic Pada Pasien Ckd Stage V yang Menjalani Hemodialisis di Rumah Sakit Indriati Solo Baru - Purwanti, Okti Sri; Mujannidah, Afidatul; Purbaningtyas, Sinta Ayu; Diniyah, Ulfa Munawaroh; Kurniasari, Dyan (Universitas Pahlawan Tuanku Tambusai, 2024)
Cronic Kidney Disease (CKD) is a condition in shich the kidney are damaged and cannot filter blood properly. Intradialytic hypertension is a well-known complication with incidence of 5-15% in CKD patiensundergoing routine hemodialiysis, but has not received much attention. One of the non pharmacological therapies tahta can be used will undergoing hemodialysis to lower blood pressure is intradialytic exercise. this study to aims to determine the effect of intradialytic exercise on intradialytic hypertension in CKD Stage V patiens undergoing hemodialysis. This research is a quasi experimental study with one group pretest posttest. The sampling technique use purposive sampling with total sample of 15 patients. Pastiens undergoing intradilysis were aged >50 years in 5 patients and were aged <50 years in 10 patients. after intradilytic exercise, the result obtained were P-value =0.004 so that the result obntained showed that there was an effect intradialytic exercise on hypertension intradialytic in CKD Stage V patient hemodialysis. Keywords: intradialytic exercise, intradialiytic hypertension, hemodialysis.